AROZ AS A REASON FOR RECREATING DEVIATIONS OF SOUNDS AND WORDS IN CLASSICAL KURDISH POETRY DIWANI MALA JAZIRI AN EXAMPLE - Mohammed, Barzan; Ilyas, Barzan (Humanities Journal of University of Zakho, 2024)
There are some important dimensions to the awakening of the literary language because the language is known mainly in literary texts, and remembering the text itself resorts to several different dimensions that differ if we look at one of them, which are the dimensions of deviation, especially in creating the problems of poems, because deviation plays an effective role in awakening the literary language. The development of literary language. We can say that deviation is the way to distinguish literary language from ordinary language, deviation in the level of difference in the language, such as vowels and consonants, deviations in the level of sound that increase, decrease, or change, or most of what occurs, at the transaction level, an action preceded. Treatment and its delay in general, although it had its effect on the poetry of Mullah Al-Jaziri in creating the weight and rhythm of his poems, as one, how much of a positive effect the deviation had on the poems that it showed.